STIGMA, DISCRIMINATION AND - Mncube, Zwelibanzi Emmanuel (My University, 2011)
One aspect of HIV/AIDS that remains a burning issue for many researchers, health workers and health institutions like Masoyi ACTS Clinic, a healthcare centre in Mpumalanga Province, South Africa that treats chronic diseases, is that HIV/AIDSrelated stigma and discrimination (S and D) threatens to continue to undermine any progress made in the areas of prevention, treatment and support. Social responses of fear, denial, stigma and discrimination continue to accompany the epidemic. The purpose of this study was to determine how people living in Masoyi area perceive HIV/AIDS-related stigma and discrimination, their experience of it and the way they are dealing with it. A qualitative study using semi-structured interviews was used. One of the main findings of the study of the focus groups in the area was that while HIV/AIDS-related stigma and discrimination are prevalent, both internalized and perceived stigma and discrimination were much more prevalent than the external stigma and discrimination. Stigma and discrimination were found to be primarily driven by fear of perceived or felt stigma and physical, social, verbal or institutional stigma and discrimination were only secondary drivers. The study calls for a new thinking when dealing with stigma and discrimination. This new thinking should take cognizance of the influence of internalized stigma on people living with HIV/AIDS.
MM - P&DM
Keywords: HIV/AIDS in rural areas